Chapter Quando le guide sono i ragazzi: una mostra sulla Resistenza. L'esperienza della II C della scuola secondaria di primo grado "I.C. Lorenzo Bartolini" di Vaiano (Prato) - Oddone, Maria Giulia (Public History of Education. Teorie, esperienze, strumenti, 2022)
The paper aims at dealing with the didactic experience realized between 2018 and 2019 in two classes of the comprehensive school Bartolini in Vaiano, near Prato. After some meeting with a local expert, and the utilisation of a laboratorial didactic, the class has realised an exhibition about the Resistance movement and it concentrates it on the character of Licio Nencetti, a partisan dead in 1944.